Inadequate lumbar protection with load weight limits based on body weight percentages: An experimental and simulation study of the weight limits set by the Japanese guidelines for preventing low back pain - Fuyuki Oyama; Tanghuizi Du; Kazuyuki Iwakiri (PLoS ONE, 2025)
Work-related low back pain is the most prevalent occupational disease in Japan, with 25% of cases resulting from manual handling of heavy loads. The Ministry of Health, Labor and Welfare of Japan has issued guidelines limiting load weights based on the worker’s body weight percentage: 40% of the body weight for males and 24% for females. This study aimed to evaluate the effectiveness of these weight limits in preventing excessive lower back strain and identify potential shortcomings. A total of 20 healthy participants (10 males and 10 females) were included in this study. The motions of the participants while holding loads at specific positions and lifting loads from the floor were recorded using a three-dimensional motion analysis system. The compressive force on the L5-S1 intervertebral disc (IVD-CF) was estimated by simulations using inverse dynamics analysis. The body weights for the musculoskeletal models were set at 50, 70, and 90 kg for males and 40, 55, and 70 kg for females, representing the light, average, and heavy body weights of Japanese workers. The load weights were set at 40% of the body weight for males and 24% for females. Increased body weight led to higher IVD-CF in males, exceeding the safe limit of 3400 N. Additionally, light-weight males experienced excessive strain when holding loads at shin height or lifting from the floor. The IVD-CF for females was lower than that for males because of their lighter body weight and load weight. However, heavy-weight females experienced excessive strain when holding loads at low and distant positions and during lifting. These findings indicate that weight limits based on body weight do not adequately prevent excessive lower back strain, and the nature of the task should be considered to avoid lower back strain.